Effects of parental presence/absence on the size of children's human figure drawings - Payne, Monica Anne
This study examined the effects of parental presence or absence in the home on the size of male and female human figure drawings by 480 children (aged 7 years to 13 years 11 months) in Barbados. Most children of both sexes drew larger female than male figures, but significant effects relating to mother absence and father absence were found for boys and girls, respectively
doi: 10.2466/pms.1990.70.3.843
Keywords: Drawings